The Development and Psychometric Validation of the Fainareti Screening Tool for Perinatal Mental Health in Greek Pregnant Women - Maria Dagla; Irina Mrvoljak-Theodoropoulou; Vassilis Daglas; Evangelia Antoniou; Eleni Rigoutsou; Alexandros Papatrechas; Calliope Dagla; Eleni Tsolaridou; Despoina Karagianni (Clinics and Practice)
Background/Objectives: It would be helpful for primary healthcare professionals to have access to a brief, general screening tool allowing them to detect patients suffering from major mental illness. This also holds for organizations and institutions at which pregnant women ask for support during the perinatal period. An evaluation of the psychometric properties, validity, and reliability of the Fainareti mental health screening tool was carried out in Greek women in this study. Methods: The study participants consisted of 518 women retrospectively followed from pregnancy to their first year postpartum as part of a health intervention at the Day Center for Women’s Mental Health Care (Perinatal Mental Health Disorders), operated by the non-profit organization Fainareti. Alongside the newly developed screening tool, this study utilized the Perinatal Anxiety Screening Scale (PASS), the Patient Health Questionnaire (PHQ-9), and the Edinburgh Postnatal Depression Scale (EPDS). Results: The assessment of the tool’s internal reliability included computing two separate internal consistency indices, with both indicating its significant level of reliability. The correlation analysis between the tool and the scales included in this study demonstrated the tool’s strong convergent validity, while factor analyses confirmed its satisfactory construct validity. Conclusions: Overall, these findings suggest that the one-factor Fainareti mental health screening tool is suitable for initial assessments of the mental health of Greek women.